2020
DOI: 10.1002/jso.26215
|View full text |Cite
|
Sign up to set email alerts
|

Is nonanatomic rectal resection a valid therapeutic option for rectal gastrointestinal stromal tumors? A proposed decision algorithm

Abstract: Background and objectives: The best surgical approach to rectal gastrointestinal stromal tumors (GISTs) is still debated, and both nonanatomic rectal resection (NARR) and anatomic rectal resection (ARR) are applied. The aim of this study was to evaluate the feasibility and oncological outcomes of NARR and ARR for rectal GISTs (R-GISTs). Methods: Through a large French multicentre retrospective study, 35 patients were treated for R-GIST between 2001 and 2013. Patients who underwent NARR and ARR were compared. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Thrity five studies were ultimately included for final analysis 6 ,. 12 , 13–46 An additional study meeting the inclusion criteria was identified from citation searching, 47 bringing the total number of final included articles to 36. The PRISMA flow diagram (Figure 1) outlines the study selection process and details the rationale for study exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Thrity five studies were ultimately included for final analysis 6 ,. 12 , 13–46 An additional study meeting the inclusion criteria was identified from citation searching, 47 bringing the total number of final included articles to 36. The PRISMA flow diagram (Figure 1) outlines the study selection process and details the rationale for study exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…To date, several studies have compared the surgical and oncological outcomes of LE and RE for rectal GISTs (11)(12)(13)(14), but some have limited numbers of small series. This study aims to systematically review available literature to compare the impact of LE and RE in localized rectal GIST patients on R0 resection, operation duration, length of stay, recurrence, and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Multimodal treatment of these tumors is different and surgical strategies vary in those patients who require resection (e.g., lymphadenectomy, e.g., dimension of resection margins etc.) [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%